2021
DOI: 10.3390/ani11123557
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Biotechnological Value of Marine Invertebrates: A Closer Look at the Biochemical and Antioxidant Properties of Sabella spallanzanii and Microcosmus squamiger

Abstract: Sabella spallanzanii and Microcosmus squamiger were profiled for proximate composition, minerals, amino acids, fatty acids (FA), carotenoids, radical scavenging activity on the 2,2-diphenyl-1- picrylhydrazyl (DPPH) radical, oxygen radical absorbance capacity (ORAC) and iron and copper chelating properties. Microcosmus squamiger had the highest level of moisture and crude protein, S. spallanzanii was enriched in crude fat and ash. Both species had similar levels of carbohydrates and energy. There was a prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 118 publications
1
0
0
Order By: Relevance
“…Moreover, iron overload is also a critical feature contributing to ferroptosis. In line with a previous study, which suggested FX as the ROS scavenger and iron-chelating substrate in the vitro experiment, 49 our findings showed that FX inhibited intracellular ROS and lipid peroxidation as well as removed excessive Fe 2+ stimulated by HR injury in NRCs. Theoretically, the reduction of FTH indicated that the stored iron was released into the cytoplasm and became free iron.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, iron overload is also a critical feature contributing to ferroptosis. In line with a previous study, which suggested FX as the ROS scavenger and iron-chelating substrate in the vitro experiment, 49 our findings showed that FX inhibited intracellular ROS and lipid peroxidation as well as removed excessive Fe 2+ stimulated by HR injury in NRCs. Theoretically, the reduction of FTH indicated that the stored iron was released into the cytoplasm and became free iron.…”
Section: Discussionsupporting
confidence: 93%
“…Since the suitability and sustainability of vegetable ingredients in diets for carnivorous fish have been increasingly questioned (5), other resources need to be explored, including ingredients that do not compete directly with the human food supply. Low-trophic marine species, such as polychaetes, have a well-balanced nutritional profile with high protein content and the ability to accumulate high levels of w3 long-chain polyunsaturated fatty acids (LC-PUFA) and have shown potential to be included in aquafeeds (6)(7)(8). Moreover, marine polychaetes have been reported as a valuable source of bioactive compounds, including chitin and chitosan, which have been described as potential functional ingredients through their antimicrobial and anti-inflammatory actions and modulation of fish gut microbial communities (9).…”
Section: Introductionmentioning
confidence: 99%